Nem-kognitív készségek mérése az oktatási integrációs program hatásvizsgálatában - Gábor Kézdi; Éva Surányi (Hungarian Academy of Sciences, Institute of Economics, 2010)
– Measuring non-cognitive skills in evaluations of education policy interventions is an increasingly important task. At the same time, choosing the adequate measures is difficult. Contrary to cognitive development, there is a shortage of reliable and valid measures of personality and behavioral traits that can be used in large scale longitudinal evaluations or in any other research contexts where time constraints limit the number of adoptable questionnaire items. Our study presents the theoretical background and the details of the design of the measurement instrument adopted in the evaluation of the education integration program launched by the National Integration Network (OOIH) of Hungary in 2003. It also demonstrates general points of the design of such measurement instruments. The results and methods of the impact evaluation research were criticized in a paper published (in Hungarian) in Magyar Tudomány, March 2010. This study answers the criticism on the measurement of non-cognitive skills. A separate study answers the criticism of sampling and methodology. In both papers we show that the critiques are unfounded.
Keywords: I20; I38; C81; 330; Bildungspolitik; Bewertung; Qualifikation; Messung; Wirkungsanalyse; Ungarn